SAT0425 NOVEL COMPUTER-ASSISTED METHODOLOGY FOR QUANTITATIVE ASSESSMENT OF MRI TREATMENT RESPONSES TO APREMILAST IN PATIENTS WITH PSORIATIC ARTHRITIS. (13th June 2020) - Bird, P.; Boesen, M.; Hinton, M.; Sanverdi, E.; Hagoug, R.; Sabin, C.; Nakasato, P.; Guerette, B.; Kubassova, O.
Abstract : Background: Response to treatment in psoriatic arthritis (PsA) can be captured using the OMERACT PsA Magnetic Resonance Imaging Score (PsAMRIS). While reliable and valid, PsAMRIS interpretation requires a trained reader to assess inflammatory lesions such as synovitis and flexor tenosynovitis on a discrete scale ranging from 0 to 3, which might not have sufficient sensitivity to capture early and subtle changes in inflammation in small cohorts. Objectives: To propose a novel computer-assisted imaging quantitative methodology to assess early response to treatment on a continuous scale and compare its results with those of PsAMRIS. Methods: Patients with active PsA in the hand and wrist were treated with apremilast 30 mg twice daily after a 5-day titration period. A total of 29 patients underwent MRI scans at baseline and months 3, 6, and 12. Images were scored for synovitis using the PsAMRIS interpreted by an experienced reader and were read in blinded sequences. Images for 13 patients with involvement of the wrist and metacarpophalangeal (MCP) joints and MRI available at baseline, 3 months, and 6 months were further processed using a novel computer-assisted imaging quantitative methodology. Images were scored concurrently, with the reader blinded to the order of visits. An experienced reader pre-defined regions of interest (ROIs) around the wrist, MCP joints (MCP-2 to MCP-5), and flexor and extensor tendons of the fingers and wrist (as applicable) with adjacent blood vessels and possible artifacts excluded from ROIs. From these ROIs, the normalized volume of inflammation (NormI) was calculated in each joint and tendon. This was done by automatically counting the pixels that were enhanced above the intensity level of a muscle. Each enhanced pixel was given a weight corresponding to the degree of enhancement, allowing differentiation of areas of residual inflammation and high perfusion. This method has been validated, tested, and implemented in the CE/FDA510-cleared software package Dynamika (IAG, Image Analysis Group). PsAMRIS responses were compared with those of the computer-assisted imaging quantitative methodology at baseline, 3 months, and 6 months. A heat map of normalized intensities was produced, highlighting areas of perfusion higher than that of healthy muscle. Changes from baseline were tested for significance using a t -test. Patients with non-missing data were included in the final statistical analysis. Results: The generated NormI map highlighted a reduction in wrist inflammation activity after 3 and 6 months of treatment with apremilast. In all cases, a downward trend in inflammatory activity in the wrist and MCP joints was observed at 3 months, indicating a reduction following treatment with apremilast (Figures 1 and 2 ). Similar improvements were observed in tenosynovitis (Figures 1 and 2). Conclusion: In this pilot assessment, apremilast was associated with improvements in synovitis and tenosynovitis over a period of 6 months using PsAMRIS. Assessment of images using NormI, a methodology allowing quantification of inflammatory activity within a joint or tendon, demonstrated the same trends over 6 months. Further studies are planned to determine the sensitivity of this novel computer-assisted imaging quantitative methodology relative to that of PsAMRIS and whether it could be used to provide early indications of treatment response in small cohorts of patients. Disclosure of Interests: Paul Bird Consultant of: AbbVie, Celgene Corporation, Eli Lilly, Janssen, Novartis, Pfizer – advisor, Speakers bureau: AbbVie, Celgene Corporation, Eli Lilly, Janssen, Novartis, Pfizer, Mikael Boesen Consultant of: AbbVie, AstraZeneca, Eli Lilly, Esaote, Glenmark, Novartis, Pfizer, UCB, Paid instructor for: IAG, Image Analysis Group, AbbVie, Eli Lilly, AstraZeneca, esaote, Glenmark, Novartis, Pfizer, UCB (scientific advisor)., Speakers bureau: Eli Lilly, Esaote, Novartis, Pfizer, UCB, Mark Hinton: None declared, Eser Sanverdi Employee of: Image Analysis Group – employment, Romiesa Hagoug Employee of: Image Analysis Group – employment, Christoper Sabin Employee of: Image Analysis Group – employment, Priscila Nakasato Employee of: Amgen Inc. – employment; Celgene Corporation – employment at the time of study conduct, Benoit Guerette Employee of: Amgen Inc. – employment; Celgene Corporation – employment at the time of study conduct, Olga Kubassova Shareholder of: IAG, Image Analysis Group, Consultant of: Novartis, Takeda, Lilly, Employee of: IAG, Image Analysis Group